New trade agreement in Asia : liberalisation in times of geopolitical rivalry - Hilpert, Hanns Günther (2021)
Zusammenfassung: With the signing of the Regional Comprehensive Economic Partnership (RCEP) on 15 November 2020, the announcement of the EU-China Comprehensive Agreement on Investment (CAI) on 30 December, and the prospects of enlarging the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), trade policy with and within Asia is gathering speed. In the greater East Asia region, consisting of Japan, South Korea, China and the Association of Southeast Asian nations (ASEAN), economic integration via trade, investment, supply chains and digital connectivity will accelerate. In contrast, regions that remain on the outside - i.e. North America, Europe and India - surely fear that trade flows will be diverted. At the same time, geopolitics have become a determining factor of trade policy. Any agreement also represents political positioning in the context of the Sino-American rivalry, or at least a reinsurance against the risks of economic or technological decoupling. What are the economic and political perspectives of these trade and investment agreements? What goals and strategies are the relevant actors pursuing? And what are the consequences for Europe’s trade policy?